2014
DOI: 10.1177/1470320314534510
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between three X-linked genes and the risk for hypertension among northeastern Han Chinese

Abstract: Our findings demonstrate that genetic defects in AGTR2 and apelin genes by themselves may play an independent leading role in determining susceptibility to hypertension in both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…[ 6 ] Nevertheless, other results showed the rs2106809 was no significant deviation in either hypertensive or normotensive women in Chinese Han population. [ 11 , 12 ] The possible reasons may be attributed to that the observed population have different ethnicity and race, and come from regions with different natural environment. Therefore, to more precisely elucidate the role of ACE2 SNPs in EH, further research is necessary to determine a wider range of ACE2 polymorphic loci associated with EH in population who come from different regions and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Nevertheless, other results showed the rs2106809 was no significant deviation in either hypertensive or normotensive women in Chinese Han population. [ 11 , 12 ] The possible reasons may be attributed to that the observed population have different ethnicity and race, and come from regions with different natural environment. Therefore, to more precisely elucidate the role of ACE2 SNPs in EH, further research is necessary to determine a wider range of ACE2 polymorphic loci associated with EH in population who come from different regions and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Only 5 polymorphisms in apelin/APJ system were significantly associated with hypertension, obesity and onset age of hypertension. The results of this pilot study were subsequently validated by several association studies [10, 12, 15, 23]. However, significant findings are not often reproducible, and no consensus has been reached yet.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, this gender-specific contribution may reflect the impact of some genes on sex chromosomes, such as apelin and angiotensin-converting enzyme 2 in X chromosome [24]. Several lines of evidence have suggested a heterogeneous contribution of these X-linked genes to the pathogenesis of hypertension [15, 25–27]. In spite of the null association of apelin gene with hypertension in this study, we observed that SBP differed significantly between two homozygous genotypes of rs3761581 in apelin gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 One study based on Eastern China (Shanghai) population did not find a significant relationship of rs56204867 and hypertension in both males ( p =0.07) and females ( p =0.4621). 16 In the Northeastern Chinese population (Heilongjiang), one study demonstrated the significant association between rs56204867 and hypertension in both females ( p =0.001) and males ( p =0.001), 20 which was absent in another study ( p =0.922 for males and p =0.251 for females). 13…”
Section: Introductionmentioning
confidence: 94%